The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1161/01.atv.19.6.1541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lovastatin Therapy on Susceptibility of LDL to Oxidation During α-Tocopherol Supplementation

Abstract: Abstract-A randomized, double-masked, crossover clinical trial was carried out to evaluate whether lovastatin therapy (60 mg daily) affects the initiation of oxidation of low density lipoprotein (LDL) in cardiac patients on ␣-tocopherol supplementation therapy (450 IU daily). Twenty-eight men with verified coronary heart disease and hypercholesterolemia received ␣-tocopherol with lovastatin or with dummy tablets in random order. The two 6-week, active-treatment periods were preceded by a washout period of at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 69 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…One study conducted in mice demonstrated that low and high doses of RYR (monacolin K, respectively, 15 and 75 mg/kg body weight) induced a dramatic decline in CoQ10 levels in the heart and liver (Yang, 2005). Clinical trials conducted with lovastatin or atorvastatin at respectively 60 and 10 mg daily showed a decrease of plasma CoQ10 levels (Palomaki, 1998;Liu, 2010). In our study, a downward trend was observed in the NCLS group for CoQ10 levels (p = 0.0682).…”
Section: Discussionsupporting
confidence: 50%
“…One study conducted in mice demonstrated that low and high doses of RYR (monacolin K, respectively, 15 and 75 mg/kg body weight) induced a dramatic decline in CoQ10 levels in the heart and liver (Yang, 2005). Clinical trials conducted with lovastatin or atorvastatin at respectively 60 and 10 mg daily showed a decrease of plasma CoQ10 levels (Palomaki, 1998;Liu, 2010). In our study, a downward trend was observed in the NCLS group for CoQ10 levels (p = 0.0682).…”
Section: Discussionsupporting
confidence: 50%
“…For instance, lovastatin administration to rats has been described to result in a significantly increased liver membrane peroxidizability (Lankin et al, 2007), as would be indicative of a loss of GPx4. Moreover, LDL from patients treated with statins has been shown in several studies to possess decreased antioxidative capacity if properly isolated (Palomä ki et al, 1999;Lankin et al, 2003). Still, it is important to note that the latter parameters reflect specific aspects of intracellular antioxidative capacity (the LDL precursor is assembled intracellularly); hence, their prooxidative response to statin treatment is not contradictory to reports describing antioxidative effects of statins regarding certain plasma/endothelial markers of oxidative stress (Rosenson, 2004).…”
Section: Statin-induced Selenoprotein Suppression 1427mentioning
confidence: 97%
“…Ubiquinol is a first-line antioxidant of plasma LDL and also protects α-tocopherol contained in this fraction from oxidation (de Rijke et al 1997). Treatment with statins reduces UQ content expressed per unit of plasma LDL cholesterol, which may increase the oxidizability of these lipoproteins (Human et al 1997;Oranje et al 2001;Palomaki et al 1997Palomaki et al , 1999. Coadministration of 180 mg/day UQ corrected enhanced LDL oxidizability in lovastatin-treated patients (Palomaki et al 1998).…”
Section: Oxidizability Of Plasma Ldlmentioning
confidence: 99%